Predictors of measles vaccination coverage among children 6–59 months of age in the Democratic Republic of the Congo. Issue 4 (25th January 2018) - Ashbaugh, Hayley R.; Hoff, Nicole A.; Doshi, Reena H.; Alfonso, Vivian H.; Gadoth, Adva; Mukadi, Patrick; Okitolonda-Wemakoy, Emile; Muyembe-Tamfum, Jean Jacques; Gerber, Sue K.; Cherry, James D.; Rimoin, Anne W.
Highlights: DRC's overall measles vaccination coverage level of 70% is too low to halt the spread of measles. Socioeconomic variables and residence are associated with vaccination coverage disparities. Vaccination coverage and data quality are linked, and as such, dated records must be increased. Abstract: Background: Measles is a significant contributor to child mortality in the Democratic Republic of the Congo (DRC), despite routine immunization programs and supplementary immunization activities (SIA). Further, national immunization coverage levels may hide disparities among certain groups of children, making effective measles control even more challenging. This study describes measles vaccination coverage and reporting methods and identifies predictors of vaccination among children participating in the 2013–2014 DRC Demographic and Health Survey (DHS). Methods: We examined vaccination coverage of 6947 children aged 6–59 months. A multivariate logistic regression model was used to identify predictors of vaccination among children reporting vaccination via dated card in order to identify least reached children. We also assessed spatial distribution of vaccination report type by rural versus urban residence. Results: Urban children with educated mothers were more likely to be vaccinated (OR = 4.1, 95% CI: 1.6, 10.7) versus children of mothers with no education, as were children in wealthier rural families (OR = 2.9, 95% CI: 1.9, 4.4). At the provincial level, urban areas more frequently reported vaccination via dated card than rural areas. Conclusions: Results indicate that, while the overall coverage level of 70% is too low, socioeconomic and geographic disparities also exist which could make some children even less likely to be vaccinated. Dated records of measles vaccination must be increased, and groups of children with the greatest need should be targeted. As access to routine vaccination services is limited in DRC, identifying and targeting under-reached children should be a strategic means of increasing country-wide effective measles control.